STUDY OF ELECTRON SCANNING MICROSCOPE INDICATORS OF A NITROGEN-CONTAINING AURIN COMPOUND - Gulboeva, Dilafruz Gulboeva; Smanova, Zulayxo; Diyorov, Zafar (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
It is known, that during the production of polyvinyl chloride in industry, chlororganics are release as a by-product. These additional decoupling chlororganics were isolated and sorbent agents were created from the amines produced by the processing. The sorbents obtained during the practical experiments of the study were establish to be use to treat industrial wastewater Cu (II) and Zn (II) ions. In order to study the indicators of the location and uniform distribution of the elements contained in the sorbent obtained during practical experiments, the scanner was analyze using an electron microscope.